(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the strategies for identifying intimate partner violence in pregnant women and the behaviors applied by Basic Health Unit nurses in the city of Rio de Janeiro. Method: descriptive, exploratory, qualitative, with 10 nurses who worked in prenatal consultations. The research took place from August 2018 to March 2019, in two UBS in Rio de Janeiro, Brazil. Semi-structured and individual interviews were used. The thematic analysis identified two categories: the first deals with the identification of violence against women perpetrated by an intimate partner (IPV) in pregnant women; and the second, the behavior of nurses in the face of IPV. Results: most participants were female, brown and aged between 25 and 60 years. The IPV identification strategies were bonding, facial expressions and the presence of the partner in the consultations. Work overload, fear, insecurity and gender issues were the reasons that supported the nurses’ conduct. Conclusion: it is necessary to train nurses and to incorporate the theme into the curricula of undergraduate and graduate courses, in order to provide support for actions to prevent and cope with IPV.